Storytelling as a managerial tool in tourism destinations: actors, processes and relations. (2016) - Gravili, Silvia; Rosato, Pierfelice
The rise of new business models has required tourism destinations to adopt appropriate tools for the construction and promotion of their identity based on sociality, emotions, interaction and connectivity. The objective of this paper is to analyse actors, actions, processes and relations that relate to the development of storytelling practices in the management of tourism destinations, analysing critical aspects linked to the generation of content and the narration of territories. The study was conducted following the qualitative methodology of multiple case studies.